Strategy to Address Private Location Cardiac Arrest: A Public Safety Survey. (2nd November 2018) - Blackwood, Jennifer; Eisenberg, Mickey; Jorgenson, Dawn; Nania, James; Howard, Bryan; Collins, Bryan; Connell, Peter; Day, Tim; Rohrbach, Cody; Rea, Thomas
Abstract: Objective : Most cardiac arrests occur in the private setting where response is often delayed and outcomes are poor. We surveyed public safety personnel to determine if they would volunteer to respond into private locations and/or be equipped with a personal automated external defibrillator (AED) as part of a vetted responder program that would use smart geospatial technology.Methods : We conducted an anonymized survey among personnel from fire-based emergency medical services (EMS) and search and rescue organizations from Washington State. The goal of the survey was to evaluate whether there was interest among cardiopulmonary resuscitation (CPR)-trained, public safety personnel to respond with or without an AED to private-residence cardiac arrest outside of working hours using a smartphone platform. We used a 5-point Likert scale to assess responses.Results : Overall the response rate was 73.7% (527/715). Two-thirds of respondents were between the ages of 30–59 with a similar proportion certified as a firefighter–emergency medical technician (EMT). Most were male (80%). As a vetted volunteer responder, the majority would "almost always" or "often" respond to private (79.7%) or public locations (85.2%) outside of work hours. The majority (54.1%) would store the AED in their vehicle while 38% would plan to keep the AED on their person. A total of 83% were "definitely' or "probably interested" in participating in the program.Conclusion : The results of this survey indicate that public safety personnel are willing to respond to suspected cardiac arrest during off-hours using geospatial smart technology to private locations with or without an AED.